Comparative Analysis of Heat Release, Bound Water Content and Compressive Strength of Alkali-Activated Slag-Fly Ash - Joseph, Shiju; Cizer, Özlem (Frontiers in Materials, 2022)
Optimizing the mix composition of alkali activated materials are at times overwhelming. This is due to the higher number of potential parameters that could be varied compared to designing a mix based on Portland cement. The present work focuses on understanding the correlations between compressive strength, bound water content and heat release from calorimeter. Different proportions of slag and fly ash are studied at two different solution to binder (S/B) ratios. Alkali solutions are made with 50% 5M NaOH and 50% water glass. Results indicate that at similar S/B ratios mixes with high amounts of slag develop high compressive strength that corresponds to high bound water contents until 28 days and high heat release until 7 days. A good correlation exists between compressive strength with cumulative heat release and bound water content, when the water to solid ratio of the initial mixture is also considered. These findings promise a less tedious method that could be employed for the optimization process for mix design of alkali activated materials.